1997
DOI: 10.1016/s0029-7844(97)00155-5
|View full text |Cite
|
Sign up to set email alerts
|

Maternal oxygen desaturation with intravenous magnesium therapy

Abstract: Maternal oxygen desaturation occurs commonly with intravenous magnesium therapy, does not occur more frequently with simultaneous administration of intravenous phenobarbital, and does not cause decompensation in maternal or fetal status. Multiple gestation may be associated with lower maternal oxygen saturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…13,14 In the current study, and supported by our Delphi consensus group, SpO 2 < 90% was a component of the combined adverse maternal outcome. As the PIERS study aims to predict outcomes, only the pulse oximetry readings before an adverse outcome were used and, therefore, there are no values for SpO 2 < 90% in the PIERS database.…”
Section: Predicted Probability Predicted Probabilitysupporting
confidence: 66%
See 2 more Smart Citations
“…13,14 In the current study, and supported by our Delphi consensus group, SpO 2 < 90% was a component of the combined adverse maternal outcome. As the PIERS study aims to predict outcomes, only the pulse oximetry readings before an adverse outcome were used and, therefore, there are no values for SpO 2 < 90% in the PIERS database.…”
Section: Predicted Probability Predicted Probabilitysupporting
confidence: 66%
“…In order to prevent overreporting of adverse outcomes resulting from the side effects of magnesium sulphate use, this study used a Glasgow Coma Scale score of < 13 (rather than < 15) as the criterion for adverse outcome to account for the drowsiness associated with magnesium sulphate use. In examining the relationship between preeclampsia, magnesium sulphate, and SpO 2 , Thorp et al 13 did not find a higher risk of oxygen desaturation in women with preeclampsia than in women receiving magnesium sulphate for other reasons; SpO 2 < 90% was used as the definition of oxygen desaturation.The major weakness of this study is that 489 women (25%) in the PIERS database were excluded because they did not have SpO 2 recorded within 48 hours of eligibility and before occurrence of an adverse outcome, yet 60 of these women (12.3%) experienced one or more components of the combined adverse maternal …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respiratory failure may result if these conditions are ignored. Although some previous studies reported that desaturation episodes did not cause decompensation in maternal and fetal status, a continuous pulse oximeter was available for added vigilance in those studies, and treatment was started as soon as desaturation was detected [16, 17]. …”
Section: Discussionmentioning
confidence: 99%
“…Hypoxaemia has been defined as SaO2 of < 94%; < 92%; < 90%; or PaO 2 < 60 mm Hg or < 8 kPa by various authors (7,8,10,12). We defined oxygen desaturation as SpO 2 < 94% as proposed by O'Driscoll et al (7).…”
Section: Discussionmentioning
confidence: 99%